Sustaining change in organizations - Hodges, Julie; Gill, Roger (Los Angeles SAGE, 2015)
Indispensable to understanding change, this unique text provides a comprehensive examination of how change can be sustained within organizations today. Featuring critical insights into theoretical concepts and current international examples, the book provides an accessible way for students to enhance their understanding and develop the crucial skills need to be successful when managing and leading change in organisations. Key Features: * Synthesizes what is known about change in organizations and then provides practical ways of sustaining it * Contains an international range of case studies and interviews which link theory to practice throughout * Explores key contemporary topics such as power, politics, ethics and sustainability for an enhanced understanding of current debates and issues * Activities, discussion questions and further reading in each chapter test your understanding of the key concepts and reinforce your learning * End of book Glossary defines key terms, for those new to studying change. * Comes with access to additional resources for students and lecturers including relevant SAGE journal articles to encourage wider reading.
Introduction to organizational change and transformation -- Theoretical approaches to change and transformation -- Leading change -- Managing change -- The drivers for change and transformation -- Diagnosing the need and readiness for change -- Planning and implementing change -- Organizational development (OD) and organizational learning -- Changing organizational structures -- Communication and change -- The nature, impact and management of attitudes towards change -- Power, politics and conflict during change -- Ensuring sustainable change through monitoring and measurement -- Contemporary issues in change and transformation -- Conclusion.
Jonathan De la Cerna (Recommending faculty) - Bookfair2017
Includes bibliographical references (pages 449-486) and index.
Also issued online.
Keywords: Organizational change -- Management